Training to Improve Language Outcomes in Cochlear Implant Recipients - Ingvalson, Erin M.; Wong, Patrick C. (Frontiers in Psychology, 2013)
Cochlear implants (CI) have brought with them hearing ability for many prelingually deafened children. Advances in CI technology have brought not only hearing ability but speech perception to these same children. Concurrent with the development of speech perception has come spoken language development, bringing with it the hopes that prelingually deafened CI recipient children will develop spoken language capabilities on par with those of normal hearing (NH) children. Unfortunately, this has not been the case, and many CI recipient children lag behind their NH peers with large variability in outcomes. It is likely that CI recipient children struggle to develop spoken language at NH-like levels because they have deficits in both auditory and cognitive skills that underlie the development of language. Fortunately, both the auditory and cognitive training literature indicate an improvement of auditory and cognitive functioning following training. It therefore stands to reason that if training improves the auditory and cognitive skills that support language learning, language development itself should also improve. In the present manuscript we will review the auditory and cognitive training and their potential impact on speech outcomes with an emphasis on the speech perception literature.